Business intelligence readiness factors for higher education institution - Hasan, N. A. (Asian Research Publishing Network, 2016)
Higher Education Institution (HEI) have embarked on the new style of decision-making with the aim to enhance the speed and reliability of decision-making capabilities. One of the hardest challenges in implementing Business Intelligence (BI) is the organization’s readiness towards adopting and implementing BI systems. Currently, few published studies have examined BI readiness in HEI environment. Seeing this challenge, this study aims to contribute in determining the BI readiness factors in HEI specifically in the deployment strategies. Through inductive attention to BI in HEI environment, three broad factors have been identified: a) Organizational – that concerning on business strategies, process and structure, b) Technology – involves the BI system and knowledge for managing including the sources and c) Social – the culture within organization that may influence decision-making and its processes. This paper also makes recommendations for future research.